Time-Dependent Change in Cartilage Repair Tissue Evaluated by Magnetic Resonance Imaging up to 2 years after Atelocollagen-Assisted Autologous Cartilage Transplantation: Data from the CaTCh Study. (July 2022) - Shinohara, Masashi; Akagi, Ryuichiro; Watanabe, Atsuya; Kato, Yuki; Sato, Yusuke; Morikawa, Tsuguo; Iwasaki, Junichi; Nakagawa, Koichi; Akatsu, Yorikazu; Ohtori, Seiji; Sasho, Takahisa
Objective: To elucidate the time course of magnetic resonance imaging (MRI)–based morphological and qualitative outcomes after an atelocollagen-assisted autologous chondrocyte implantation (ACI) and to analyze the correlation between arthroscopic and MRI-based assessment. Design: We included ACI recipients from a multicenter registration study (CaTCh [Cartilage Treatment in Chiba] study). Morphological (3-dimensional magnetic resonance observation of cartilage repair tissue: 3D-MOCART, MOCART2.0) and qualitative assessment (T2- and T1rho-mapping) by MRI were conducted at 6, 12, and 24 months post-implantation. Global T2 and T1rho indices (T2 and T1rho in repair tissue divided by T2 and T1rho in normal cartilage) were calculated. Arthroscopic second-look assessment was performed in 4 and 15 knees at 12 and 24 months post-implantation, respectively. Results: The 3D-MOCART over 12 months witnessed significant patient improvement, but some presented subchondral bone degeneration as early as 6 months. The MOCART2.0 improved from 57.5 to 71.3 between 6 and 24 months ( P = 0.02). The global T2 index decreased from 1.7 to 1.2 between 6 and 24 months ( P < 0.001). The global T1rho index decreased from 1.5 to 1.3 between 6 and 24 months ( P = 0.004). Normal or nearly normal ICRS-CRA (cartilage repair assessment scale developed by the International Cartilage Repair Society) grades were achieved in 86% and 93% of the lesions at 12 and 24 months, respectively. Better ICRS-CRA grade corresponded to better MOCART2.0, with no trend in the T2 and T1rho values. Conclusions: Atelocollagen-assisted ACI improved the MRI-based morphological and qualitative outcomes until 24 months post-surgery, and normal or nearly normal grades were achieved in most lesions by arthroscopic assessment. MRI assessment may be an alternative to arthroscopic assessment.